STRATEGI PENINGKATAN PENDIDIKAN KARAKTER BERBASIS PERSEPSI GURU DI SMP - Leni Yusnita; Rambat Nur Sasongko; Manap Somantri (Manajer Pendididikan, 2017)
This study aimed to describe the strategy of increasing the perception-based character education teacher at junior high school number one Bermani Ilir Kepahiang Regency. This research apprach used is descriptive qualitative because they collected and analysis is more qualitative, which aims to understand the meaning behind the they looks.The results of this study stated that the strategy  of increasing the perception-based character education teacher done through the integration of character education into everyday learning. The school has tried as much as possible to improve the srategy of character education through the process of planning, organizing, implementation, evaluation and follow-up recommendation in order to approach perfection in accordance with the applicable procedures.